Cardiac effects of current treatments of chronic obstructive pulmonary disease. Issue 2 (February 2016) - Lahousse, Lies; Verhamme, Katia M; Stricker, Bruno H; Brusselle, Guy G
Summary: We review the cardiac safety of the drugs available at present for the maintenance treatment of chronic obstructive pulmonary disease (COPD) in stable disease, focusing on inhaled long-acting muscarinic antagonists (LAMA) and long-acting β2 agonists (LABA), used either as a monotherapy or as a fixed-dose combination. We report the difficulties of, and pitfalls in, the investigation of the safety of drug treatments in COPD, which is hampered by the so-called COPD trial paradox: on the one hand, COPD is defined as a systemic disease and is frequently associated with comorbidities (especially cardiovascular comorbidities), which have an important effect on the prognosis of individual patients; on the other hand, patients with COPD and cardiovascular or other coexisting illnesses are often excluded from participation in randomised controlled clinical trials. In these trials, inhaled long-acting bronchodilators, both LAMA or LABA, or both, seem to be safe when used in the appropriate dose in adherent patients with COPD without uncontrolled cardiovascular disease or other notable comorbidities. However, the cardiac safety of LAMA and LABA is less evident when used inappropriately (eg, overdosing) or in patients with COPD and substantial cardiovascular disease, prolonged QTc interval, or polypharmacy. Potential warnings about rare cardiac events caused by COPD treatment from meta-analyses and observational studies need to be confirmed in high quality large randomised controlled trials. Finally, we briefly cover the cardiac safety issues of chronic oral drug treatments for COPD, encompassing theophylline, phosphodiesterase inhibitors, and macrolides.